Un acercamiento a la lírica de Helena Ospina en Sonata de otoño: Canción consumada - Palacios, Conny (2018)
An approach to Helena Ospina``  s lyrics is a general and ambitious title, because I want to analyze the mystical poetry of the author. It is a task that I have assigned myself in stages. On this occasion I will refer specifically to Autumn Sonata. Consummated song (1995). In this  paper I will study the mystical process involved and make reference to the symbolic use of the number three, as well as other symbols which I consider essential in her lyrics and that are present in this work.